Polygamy: A Methodological Analysis of Hadith Studies - Ramdani, Acep Dani (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2019)
Polygyny, as a marital system, has a long history that differs across cultures. Before the advent of Islam, polygyny was practiced by various ethnic groups, including the Hebrew and Arab peoples during the Jahiliyah period. In addition, there were also